Starry night : a Christmas novel - Macomber, Debbie (New Yor, Yew York; Random House Large Print, 2013)
"Carrie Slayton is a successful gossip columnist, but her dream is to become a serious journalist. Finnegan Dalton is a notorious recluse whose book about living in the Alaskan wilds skyrocketed to the top of the New York Times bestseller list. Recognizing a golden opportunity, Carrie uses a little guile in tracking down Finn's whereabouts in the snowy Alaskan wilderness outside of Fairbanks, only to discover that he truly is as mysterious and withdrawn as his reputation suggests. As she grows closer to finding out who Finn really is, Carrie will have to decide whether to respect his wishes by abandoning the story that would make her career, and Finn will have to decide whether he can open his heart again"--
Keywords: Women journalists -- Fiction; Recluses as authors -- Fiction; Christmas stories; Alaska -- Fiction; Christmas stories